2020
DOI: 10.3389/fpls.2020.00966
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Arbuscular Mycorrhizal Fungi and Phosphorus Inputs on Selenium Uptake by Alfalfa (Medicago sativa L.) and Selenium Fraction Transformation in Soil

Abstract: Selenium (Se) is a beneficial element to plants and an essential element to humans. Colonization by arbuscular mycorrhizal fungi (AMF) and supply of phosphorus (P) fertilizer may affect the bioavailability of Se in soils and the absorption of Se by plants. To investigate the interaction between AMF and P fertilizer on the transformation of soil Se fractions and the availability of Se in the rhizosphere of alfalfa, we conducted a pot experiment to grow alfalfa in a loessial soil with three P levels (0, 5, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…As P is immobilized, increasing mineral P input into the soil is a common agronomy practice used to improve productivity (Zhang et al, 2019 ). In the present study, both bulk and rhizosphere soil Olsen-P concentrations increased as P supply increased ( Figure 5 ; Supplementary Figure 5 ), which is similar to the findings observed when alfalfa was grown in a loessial soil (Peng et al, 2020 ). P is a nutrient that stimulates shoot biomass production and more importantly, acts as a regulatory signal mediating changes in root architecture (López-Bucio et al, 2003 ; Pongrac et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…As P is immobilized, increasing mineral P input into the soil is a common agronomy practice used to improve productivity (Zhang et al, 2019 ). In the present study, both bulk and rhizosphere soil Olsen-P concentrations increased as P supply increased ( Figure 5 ; Supplementary Figure 5 ), which is similar to the findings observed when alfalfa was grown in a loessial soil (Peng et al, 2020 ). P is a nutrient that stimulates shoot biomass production and more importantly, acts as a regulatory signal mediating changes in root architecture (López-Bucio et al, 2003 ; Pongrac et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Soil enzyme vigor is closely related to the function of the soil ecosystem and can reflect the metabolic capacity of soil microorganisms ( Zarea et al., 2011 ; Bowles et al., 2014 ), and microbial changes can directly affect the activity of soil enzymes ( Pereira et al., 2016 ). Some studies have shown that AMF can improve the host’s absorption of mineral elements by affecting the soil enzyme vigor ( Peng et al., 2020 ), and AMF can improve the activity of N-related enzymes in the host’s rhizosphere soil at the early stage of colonization to promote the host’s absorption of nitrogen ( Stamou et al., 2017 ). There is also a certain correlation between the change of soil enzyme vigor and the change of root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…Even under low phosphorus conditions in the Zhongning region, effective phosphorus concentration increased significantly after a few months, especially in the high-demand month of July. Perhaps, under low phosphorus availability, AMF colonization stimulated plant roots to release additional carboxylates and alkaline phosphatase ( 70 ). Overall, understanding the effects of various environmental factors on AMF communities can provide better insights into host plant growth and better crop yields.…”
Section: Discussionmentioning
confidence: 99%